Coeval perpendicular shortenings in the Brasilia belt : collision of irregular plate margins leading to oroclinal bending in the Neoproterozoic of central Brazil - Silva, Luiz José Homem D´El-Rey (2011)
The three belts which form the Tocantins province (central Brazil) records Neoproterozoic-EoPaleozoic collisions involving the Amazon and São Francisco paleocontinents and the Paraná continental block. The Brasília belt is a typical orocline bended around the WNW—ESE striking Pirineus Zone of High Strain (PZHS) and is comprised of the NE-trending (northern) and SE-trending (southern) segments. The Brasília dome is an N—S elliptical structural window situated in the center of the belt, at the eastern end of the PZHS. It evidences Di— D₂ and D₃ɴ shortenings (~ 750—590 Ma) due to ocean closure and Amazon- São Francisco collision following a WNW—ESE path, and demonstrates similar evolution for both segments of the belt. However, in the southern segment, D₁—D₂ structures are deformed by shortening in the SW-NE direction (D₃S). New data demonstrating D₁—D₂ and D₃ɴ tectonites deformed by D₃S struc- tures in the area close to the dome's SW margin and SE of the PZHS support understanding the Brasília belt and oroclinal bending as a consequence of the collision of two (Amazon and São Francisco) irregular continental margins leading to separation-rotation of the Paraná block from the Amazon paleocontinent and the Paraná-São Francisco collision.